Terrorism : a special kind of violence - Hyde, Margaret O. (Margaret Oldroyd), 1917-; Forsyth, Elizabeth Held. (New York : Dodd, Mead, 1987)
Discusses the phenomenon of terrorism, its forms, increasing frequency, historical origins, and political, religious, and psychological aspects.
Includes index.
Bibliography: p. 103-105.
7.5
7-10.
Keywords: Terrorism -- Juvenile literature; Terrorists -- Juvenile literature; Terrorism; Terrorism